Konseptualisasi Ilmu Hadis: Perspektif Ontologi, Epistemologi, dan Aksiologi bagi Pengembangan Hukum Islam - Sepmin Alfuqan; La Ode Ismail Ahmad; Sitti Asiqah Usman Ali (Advances In Education Journal, 2025)
The science of Hadith serves as an epistemological foundation ensuring the authenticity and validity of the Sunnah as a primary source of Islamic law. However, contemporary studies on Hadith tend to emphasize the technical aspects of sanad and matn criticism, while its philosophical dimensions remain underexplored. This article aims to reconstruct the conceptualization of Hadith science through three perspectives of the philosophy of science—ontology, epistemology, and axiology—and to explain its implications for the development of Islamic law. Employing a qualitative-descriptive approach and philosophical analysis of classical and contemporary sources, this study finds that ontologically, Hadith science preserves the authenticity of prophetic teachings; epistemologically, it establishes an empirical-verificative and rational system of knowledge for understanding the Sunnah; and axiologically, it directs the application of Hadith toward human welfare and the realization of maqāṣid al-sharīʿah. Thus, Hadith science is not merely a technical discipline but a dynamic system of knowledge that supports the renewal of Islamic law while maintaining authenticity, rationality, and relevance to contemporary contexts.